Clustered tree size analysis of bio-productivity of Dinghushan National Nature Reserve in China - Li, Yuelin; Nyongesah, Maina John; Deng, Libin; Haider, Fasih Ullah; Liu, Shizhong; Mwangi, Brian Njoroge; Zhang, Qianmei; Chu, Guowei; Zhang, Deqiang; Liu, Juxiu; Meng, Ze (Frontiers in Ecology and Evolution, 2023)
Variability in tree size and biomass can be observed within natural forests across heterogeneous terrain. To systematically investigate productivity based on species composition and structure of China’s forest communities, we launched a long-term project consisting of forest vegetation surveys in the Dinghushan forest complex. We grouped the trees as large or mature (DBH > 30 cm), medium-sized or growing (DBH 10-30 cm), and small-sized or regenerating seedlings (DBH < 10 cm). We measured species DBH, height, and biomass components (trunk, leaves, branches, above-ground dry weight, and below-ground dry weight). All statistical analyses were performed using SPSS 25. Linear regression analyses were used to understand the relationships between forest bio-productivity components. Total above-ground biomass was 34.19±5.75Kg/tree but varied results were obtained when the forest was clustered based on DBH. Large-sized trees contributed an average of 2400.54±510.4kg/tree (93.24%) while medium-sized trees contributed 171.61±25.06kg/tree and the least was regenerating seedlings which contributed 3.013±0.07kg/tree. There were positive linear relationships for all life forms between biomass and DHB as well as DBH and height. The evergreen broadleaved shrubs were shorter in height (3.06±0.99m) compared to palm-leaved life forms (19.29±5.39m). Height influenced biomass accumulation and hence C gain where life forms with tall stands had higher biomass. Generalized biomass estimation without clustering based on life forms or size class underestimates biomass components and hence lower C stocks for most forests in the world. It is also important to note that trees with large-sized DBH consist of tall, large, well-lit crowns that contribute to the high primary productivity of forests and therefore storage of more C.